PEMANFAATAN KULIT ALE-ALE SEBAGAI AGREGAT KASAR DALAM PEMBUATAN BETON - Suratmin, Suratmin; Satyarno, Iman; Tjokrodimuljo, Kardiyono (Civil Engineering Forum Teknik Sipil, 2007)
At present cockle shells of ale-ale are used only as materials of heaping up muddy yards or roads in Ketapang City. Therefore, it is a challange to conduct study to utilize cockle shells of aleale as aggregate for concrete. It is expected that the result of this study can not only give additional economicall value for cockle shells of ale-ale, but also reduce impacts on environment. In the present research, intact and broken cockle shells were used as concrete aggregate mixed with white sand, and white Portland cement. The amount of cement used is 300 kg/m3. The composition of both intact and broken cockle shells of applied in the research was 100%, 75%, 25%, and 0%. The specimen of intact cockle shells ale – ale was made in various shape and size namely sylinder-shaped models of ∅150 x 300 mm and ∅80 x 160 mm and a ‘concrete brick’-shaped model, while specimen broken cockle shells of ale-ale were sylinder-shaped models of ∅150 x 300 mm and ∅80 x 160 mm, a cube-shaped model of 70 x 70 x 70 mm and a ‘paving block’- shaped model. The research aims at finding the compressive strength of 28 days old, abration of concrete, and impact resistance of concrete. From the result of the research, it can be identified that the specific gravity of concrete with intact and broken cockle shells of ale-ale with the variation of 50% corresponds to a ‘normal concrete’ category. While specific gravity the intact cockle shells with variation of 50% is 2367.82, the broken cockle shells with the variation of 50% is 2302,66. Based on the result, it can also seen that with the variation of 50%, the highest compressive strength of concrete in the mixture of intact cockle shells of ale-ale is 24.98 MPa, and for broken cockle shells of ale-ale is 27.53 MPa.